Um parágrafo de história na literatura francesa: a representação do Caso Dreyfus em L'Île des pingouins, de Anatole France - Fraga, Denise [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
This thesis analyzes Book VI of L Île des pingouins (1908), by Anatole France (1884-1924). In the novel, French society is satirically represented by a group of penguins metamorphosed into men after having being mistakenly baptized by the old apostle Mael, who mistook the birds for short men. The novel is divided into eight sections called books, in order to make them look like the sacred books. The sixth book is about the Dreyfus Case (1894-1906), a case of espionage known as one of the greatest judicial errors of modern history. Capitan Alfred Dreyfus, accused of having handed in military secrets belonging to the French artillery army to the German army, was arrested and deported to the Devil s Island, where he stayed for five years, until his process was reviewed and the real spy was found out. In L Île des pingouins, the Dreyfus Case is represented in a parodical way by the Pyrot Case, in which a penguin official is unfairly accused of having handed in eighty thousand bales of hay to the porpoise enemy army. Through laughter, the reader realizes the narrator s disenchantment: the presentation of the characters as caricatures, the satire in relation to history and the positive method shows, however, a pessimistic view of the origin of the universe, of mankind and its history. Therefore, the objectives of this thesis are: i) to verify how the Dreyfus Case is recovered in Book VI of the novel, whose title is Modern Times - The Case of the Eighty Thousand Bales of Hay, by studying the effects of the usage of parody, hyperbole, and caricature in order to satirize historical figures, social institutions (such as the Church, the army, the government) and even the end of the Case; ii) to analyze the means used by the novelist to give his critical rereading of history an aesthetic feature, by examining how the writer gives literariness to historical facts, transforming them into parts of his novel.
Keywords: France, Anatole, 1884-1924 - L'Île des pingouins - Crítica e interpretação; Literatura francesa - Séc. XX - História e crítica,- Teoria, etc; Ficção francesa - Séc. XX - História e crítica,- Teoria, etc; Teoria literária; Caso Dreyfus; French literature; Dreyfus case; Anatole france